Geology and Stratigraphic Correlation of the Murray and Carolyn Shoemaker Formations Across the Glen Torridon Region, Gale Crater, Mars. Issue 9 (19th September 2022) - Fedo, C. M.; Bryk, A. B.; Edgar, L. A.; Bennett, K. A.; Fox, V. K.; Dietrich, W. E.; Banham, S. G.; Gupta, S.; Stack, K. M.; Williams, R. M. E.; Grotzinger, J. P.; Stein, N. T.; et al.
Abstract: The Glen Torridon (GT) region within Gale crater, Mars, occurs in contact with the southern side of Vera Rubin ridge (VRR), a well‐defined geomorphic feature that is comparatively resistant to erosion. Prior to detailed ground‐based investigation of GT, its geologic relationship with VRR was unknown. Distinct lithologic subunits within the Jura member (Murray formation), which forms the upper part of VRR, made it possible to be also identified within GT. This indicates that the strata pass across the geomorphic divide between regions. Furthermore, the cross‐bedded lower part of the overlying Knockfarril Hill member (Carolyn Shoemaker formation) also occurs within both VRR and GT. Correlation of both units demonstrates that the strata form a continuous stratigraphic succession regardless of large‐scale geomorphic expression. The lithologic change from mudstone (Jura member) to cross‐bedded sandstone (Knockfarril Hill member) heralds a significant shift in paleoenvironment from lacustrine to fluvial. The upper part of the Knockfarril Hill member consists of interbedded mudstone and sandstone that transitions to the overlying finely laminated mudstone of the Glasgow member, and a return to lacustrine deposition. In GT, the Stimson formation unconformably overlies the Glasgow member, where it demarks the southern boundary of GT. Contacts for each stratigraphic unit were defined and transferred to a high‐resolution image base to make a geologic map and cross sections perpendicular to the NE strike. Stratal dips cannot exceed 2° NW to retain the positions of stratigraphic units in the locations they are exposed throughout GT. Plain Language Summary: The Mars Science Laboratory Curiosity rover explored a region called Glen Torridon (GT) that is located on the northwest side of a large sedimentary central mound (Mount Sharp) within Gale crater. This study analyzed the rocks within GT to (a) identify the sedimentary features, (b) determine if or how the sedimentary layers correlate between the Vera Rubin ridge (VRR) and GT regions, (c) interpret ancient environments, (d) generate a geologic map, and (e) discuss the relationship between topography and the exposure of sedimentary layers. Even though the VRR and GT regions are very different in present‐day geomorphology, sedimentary layers correlate across the two regions indicating that the layers belong to a continuous sedimentary succession. Cross‐bedded sandstones of the Knockfarril Hill member represent a change to fluvial from the underlying lake and lake‐margin deposits of the Jura member, which represents a major shift in depositional environment. Packages of layers have distinct characteristics, which allows their distribution to be represented on a map. A geologic cross section limits the tilt of the layers to less than two degrees. We find that caution must be taken when attempting to derive primary stratigraphy only using datasets acquired from orbital platforms. Key Points: Cross‐bedded Knockfarril Hill member strata overlie mudstone of the Jura member indicating an environmental change from lake to fluvial A geologic map of Glen Torridon (GT) made using lithologically defined stratigraphic units shows that strata dip two degrees or less to the NNW Stratigraphic units pass from Vera Rubin ridge into GT indicating that strata continue through a major geomorphic boundary